2017
DOI: 10.3389/fphar.2017.00277
|View full text |Cite
|
Sign up to set email alerts
|

Azoxystrobin Induces Apoptosis of Human Esophageal Squamous Cell Carcinoma KYSE-150 Cells through Triggering of the Mitochondrial Pathway

Abstract: Recent studies indicate that mitochondrial pathways of apoptosis are potential chemotherapeutic target for the treatment of esophageal cancer. Azoxystrobin (AZOX), a methoxyacrylate derived from the naturally occurring strobilurins, is a known fungicide acting as a ubiquinol oxidation (Qo) inhibitor of mitochondrial respiratory complex III. In this study, the effects of AZOX on human esophageal squamous cell carcinoma KYSE-150 cells were examined and the underlying mechanisms were investigated. AZOX exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Bcl-2 family (including Bcl-2 and Bax) regulates intrinsic apoptosis senses of death signals ( Fox and MacFarlane, 2016 ). Previous studies have reported that the balance of Bcl-2/Bax determines the initiation of mitochondrial apoptosis, and a high ratio of Bcl-2/Bax is considered anti-apoptotic ( Shi et al, 2017 ). Caspase-9 and caspase-3 play the executioner role in apoptosis, and upon their activation, their precursor forms are cleaved ( Lopez and Tait, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bcl-2 family (including Bcl-2 and Bax) regulates intrinsic apoptosis senses of death signals ( Fox and MacFarlane, 2016 ). Previous studies have reported that the balance of Bcl-2/Bax determines the initiation of mitochondrial apoptosis, and a high ratio of Bcl-2/Bax is considered anti-apoptotic ( Shi et al, 2017 ). Caspase-9 and caspase-3 play the executioner role in apoptosis, and upon their activation, their precursor forms are cleaved ( Lopez and Tait, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Equol, which is a metabolite of daidzein, induces apoptosis in SMMC-7721 human hepatocellular carcinoma cells through the intrinsic and endoplasmic reticulum stress pathways (26). Caspase-9 and the Bcl-2/Bax ratio are commonly used activity markers of the mitochondrial apoptotic pathway (43)(44)(45). In the present study, western blotting was used to detect these markers, revealing that the cleavage of caspase-9 increased and the ratio of Bcl-2/Bax decreased in both cell lines in a dose-dependent manner, which indicated that daidzein-induced apoptosis was mediated via the mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…32,35 A ratio of Bcl-2/Bax was usually use as the basis for determining apoptosis, and an increased ratio represents anti-cell apoptosis. 36 The Bcl-2 family controls the release of cytochrome c (Cyt-c) by modulating the mitochondrial membrane permeability. 29 Caspases are a group of proteases that have a similar structure in the cyto- (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic apoptotic pathway (the mitochondrial pathway) is regulated by Bcl‐2 protein family (including anti‐apoptotic protein Bcl‐2 and pro‐apoptotic protein Bax) 32,35 . A ratio of Bcl‐2/Bax was usually use as the basis for determining apoptosis, and an increased ratio represents anti‐cell apoptosis 36 . The Bcl‐2 family controls the release of cytochrome c (Cyt‐c) by modulating the mitochondrial membrane permeability 29 .…”
Section: Discussionmentioning
confidence: 99%